Application of insertable cardiac monitors in the real world: an observational cohort study in China - Beibing Di; Lifeng Liang; Wangyang Yang; Nixiao Zhang; Xiaona Liu; Hui Peng; Zhijun Sun (BMC Cardiovascular Disorders)
Abstract Background Insertable cardiac monitors (ICMs) are increasingly used for long-term electrocardiographic monitoring. However, the data on ICMs remains limited in China. Methods In this retrospective observational study, we evaluated the real-world use and outcomes of patients consecutively receiving Reveal LINQ (Medtronic Ltd, Minneapolis, MN) devices from 2020 to 2022 at the Cardiovascular Center of Beijing Friendship Hospital. Patient characteristics, ECG parameters, ICM indications and follow-up data were collected. The outcomes including symptom documentation, arrhythmia detection and ICM-guided interventions were identified. Results A total of 200 patients (age 64 ± 14 years; 52% males) receiving ICMs were enrolled (134 syncopes, 59 unexplained palpitations, 7 cryptogenic strokes). During median follow-up of 28 months, 98 patients (49%) had documented clinically significant arrhythmia. After ICM diagnosis, 89 (44.5%) of patients had ICM-guided actionable events. Pacemaker/defibrillator implantation (48, 24%), catheter ablation (27, 13.5%) and mediation management (11, 5.5%) were the majority of ICM-derived management. For syncope, age > 65 years (HR 1.032, p = 0.017), asymptomatic sinus bradycardia (45–55 beats / min) (HR 2.106, p = 0.043) and RR interval exceeding 2 s (HR 3.625, p < 0.001) were significantly associated with actionable events. The risk of arrhythmia requiring management changes was significantly stepwise higher with the prevalence of more risk factors (P < 0.001 by log-rank). Conclusions ICM utilization is associated with high efficacy in diagnoses and triggers important and optimal management in China. Age > 65 years, asymptomatic sinus bradycardia (45–55 beats / min) and RR interval exceeding 2 s are independent clinical predictors of ICM-guided clinical management for syncope.